1‐Ethoxy‐2‐propanol [MAK Value Documentation in German language, 2018]. Issue 2 (25th April 2018) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the work place (MAK value), the Pregnancy Risk Group and absorption through the skin of 1‐ethoxy‐2‐propanol [1569‐02‐4 ]. 1‐Ethoxy‐2‐propanol is irritating to the eyes of rabbits and can damage the cornea. The critical systemic effects are pale foci in the lung and increased urine volume in rats after 13 weeks inhalation. The NAEC of these effects is estimated at 250 ml/m 3, which results in a decreased MAK value of 20 ml/m 3 (86 mg/m 3 ). This value also protects against possible irritation, as local effects are not observed up to 2000 ml/m 3 in the 13‐week rat inhalation study. Since the critical effect of 1‐ethoxy‐2‐propanol is systemic, Peak Limitation Category II is retained. There is no specific toxicokinetic data available, so that the default excursion factor of 2 is confirmed. New data on reproduction toxicity with 1‐ethoxy‐2‐propanol are not available. 1‐Ethoxy‐2‐propanol remains assigned to Pregnancy Risk Group C. Skin contact is expected to contribute significantly to systemic toxicity and 1‐ethoxy‐2‐propanol remains designated with "H".